The teaching of music history in Japanese music education - Sonoda, Midori (Musica Docta, 2014)
One of the leading institutions in the field of musicology in Japan is the one hosted by “Tokyo University of the Arts” (previously Tokyo National University of Fine Arts and Music). The musicology course, started in 1949, was, and still is, the main promoter of music history teaching in the Japanese university system. A reflection on the over 60 years of its existence, which has been characterized by the fortunate coexistence of musicology students and students of ‘practical’ musical courses, might contribute to raise awareness among European musicologists about the pedagogic-didactic task that is expected of them in the current situation of Western musical culture.